2022
DOI: 10.1039/d2sc03552a
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic asymmetric azidation of sulfoxonium ylides: mild synthesis of enantioenriched α-azido ketones bearing a labile tertiary stereocenter

Abstract: Disclosed here is a catalytic asymmetric azidation reaction for the efficient synthesis of α-azido ketones bearing a labile tertiary stereocenter. With a superb chiral squaramide catalyst, a mild asymmetric formal...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…Almost immediately, the same group also discovered an efficient organocatalytic formal N-H insertion reaction of α-keto sulfoxonium ylides 50 bearing two aryl groups and arylamines 2 using chiral phosphoric acid C14 as catalyst [Figure 17] [77] . With the developed protocol, a broad range of α-tertiary aminoketones 5 could be smoothly obtained in good to excellent yields (up to 90%) and ee values (up to 94%).…”
Section: Asymmetric X-h (X = S N C) Bond Insertion Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost immediately, the same group also discovered an efficient organocatalytic formal N-H insertion reaction of α-keto sulfoxonium ylides 50 bearing two aryl groups and arylamines 2 using chiral phosphoric acid C14 as catalyst [Figure 17] [77] . With the developed protocol, a broad range of α-tertiary aminoketones 5 could be smoothly obtained in good to excellent yields (up to 90%) and ee values (up to 94%).…”
Section: Asymmetric X-h (X = S N C) Bond Insertion Reactionmentioning
confidence: 99%
“…However, the asymmetric cyclization reaction involving sulfoxonium ylides by means of an organocatalysis tactic is rarely studied. Until recently, Bernardi, Fochi, and coworkers reported the first organocatalytic tandem cyclopropanation/ hemiaminalization reaction between 2'-hydroxycinnamaldehydes 72 and stabilized α-carbonyl sulfoxonium ylides 50 by using Jørgensen-Hayashi catalyst C17, providing cyclopropane-fused chromane derivatives 74 This figure is used with permission from the Royal Society of Chemistry [77] .…”
Section: Asymmetric Cyclization Reaction Of Sulfoxonium Ylidesmentioning
confidence: 99%
“…The Davies group developed an elegant method for silver-catalyzed insertion of vinyl diazo compounds into the carboxylic acid. , However, the stability of diazo compounds and regioselectivity for the nucleophilic addition are major concerns in this approach (Scheme a). Sulfoxonium ylides have proven to be alternative surrogates to diazo compounds for the insertion and carbene-mediated reactions. Recently, α-keto sulfoxonium ylides have been widely utilized for various X–H (X = N, O, S, C) insertion reactions under metal- and metal-free conditions. Despite the progress on the insertion reactions of α-keto sulfoxonium ylides, the chemistry of vinyl sulfoxonium ylides has been underexplored. Remarkably, our previous studies have demonstrated that the reactivity and stability of α-keto sulfoxonium ylides differ from vinyl sulfoxonium ylides .…”
Section: Introductionmentioning
confidence: 99%
“… 40 42 Recently, α-keto sulfoxonium ylides have been widely utilized for various X–H (X = N, O, S, C) insertion reactions under metal- and metal-free conditions. 42 51 Despite the progress on the insertion reactions of α-keto sulfoxonium ylides, the chemistry of vinyl sulfoxonium ylides has been underexplored. Remarkably, our previous studies have demonstrated that the reactivity and stability of α-keto sulfoxonium ylides differ from vinyl sulfoxonium ylides.…”
Section: Introductionmentioning
confidence: 99%
“… 14 Rodriguez and co-workers developed the highly stereoselective 1,4-addition of α-keto esters to nitroolefins by using Takemoto's thiourea organocatalyst. 15 Our continuous interest in developing new organocatalytic asymmetric reactions, 16 and inspiration from the work of Rodriguez and others prompted our investigation into the vinylogous Michael addition reaction of deconjugated α-keto esters. Herein, we report the successful realization of this, affording valuable enantioenriched Rauhut–Currier type products with high enantioselectivities (94–99%) upon in situ isomerization of the terminal C C double bond, which could not be accessed by direct Rauhut–Currier reaction ( Scheme 1c ).…”
Section: Introductionmentioning
confidence: 99%